2017
DOI: 10.1186/s12879-017-2754-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for multidrug-resistant pathogens in bronchiectasis exacerbations

Abstract: BackgroundNon-cystic fibrosis bronchiectasis is a chronic structural lung condition that courses with recurrent infectious exacerbations that lead to frequent antibiotic treatment making this population more susceptible to acquire pathogens with antibiotic resistance. We aimed to investigate risk factors associated with isolation of multidrug-resistant pathogens in bronchiectasis exacerbations.MethodsA prospective observational study was conducted in two tertiary-care hospitals, enrolling patients when first e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
(31 reference statements)
0
20
0
Order By: Relevance
“…The clinical microbiology laboratory has a crucial role in rapid detecting and reporting drug resistant bacteria to infectious disease specialists in order to choose appropriate antibiotic therapy. Multidrug resistant (MDR) bacteria such as carbapenem-resistant pathogens are difficult to treat even when appropriate initial antibiotic therapy is used because they require different treatment regimens to those usually recommended in guidelines [22]. Hence, reliable treatment of MDR pathogens should be based on drug susceptibility testing since only few antibiotics remain as last-resort agents.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical microbiology laboratory has a crucial role in rapid detecting and reporting drug resistant bacteria to infectious disease specialists in order to choose appropriate antibiotic therapy. Multidrug resistant (MDR) bacteria such as carbapenem-resistant pathogens are difficult to treat even when appropriate initial antibiotic therapy is used because they require different treatment regimens to those usually recommended in guidelines [22]. Hence, reliable treatment of MDR pathogens should be based on drug susceptibility testing since only few antibiotics remain as last-resort agents.…”
Section: Discussionmentioning
confidence: 99%
“…The most common isolated bacteria in the sputum cultures of patients with bronchiectasis exacerbations are Pseudomonas aeruginosa, Haemophilus influenzae, Enterobactericeae, Streptococcus pneumoniae, Staphylococcus aureus and Moraxella catarrhalis. However, it has been increasingly recognised, through clinical experience and limited evidence data that the same microorganisms are also isolated when the patient is clinically stable [30][31][32] . The challenge is clarifying why these patients exacerbate.…”
Section: Aetiology Of Exacerbationsmentioning
confidence: 99%
“…A major concern about long-term antibiotic (inhaled and oral) treatment is microbial resistance 19 . A prospective observational study by Menéndez et al 32 identified three independent risk factors associated with isolation of multidrug-resistant (MDR) pathogens in bronchiectasis exacerbations: chronic renal disease, prior MDR isolation and hospitalisation in the previous year. Notably, MDR isolation was more frequent in patients using inhaled antibiotics (34.4% versus 19.7%), but there was no statistically significant difference.…”
Section: Long-term Antibiotic Treatment -Inhaled or Oralmentioning
confidence: 99%
“…Bronchiectasis is a chronic inflammatory structural respiratory disease associated with frequent exacerbations of varying severity [ 1 , 2 ]. In general, patients with advanced disease and a high bronchiectasis severity index (BSI) [ 3 ] or a high FACED (FEV1, age, chronic colonization, extension, dyspnea) [ 4 ] score have an average of two or more exacerbations per year [ 5 ], and Pseudomonas aeruginosa is the most frequent microorganism involved [ 6 ]. It has been clearly demonstrated that exacerbations lead to lung function deterioration [ 7 ], poor prognosis [ 3 ], and increased mortality [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%